Assessing empathy in healthcare services: a systematic review of South American healthcare workers’ and patients’ perceptions - Moya-Salazar, Jeel; Goicochea-Palomino, Eliane A; Porras-Guillermo, Jorge; Cañari, Betsy; Jaime-Quispe, Alexis; Zuñiga, Nahomi; Moya-Salazar, María Jesús; Contreras-Pulache, Hans (Frontiers in Psychiatry, 2023)
Background: Empathy in healthcare service refers to the ability of healthcare workers (HCWs) to put themselves in patients' shoes, which is necessary to ensure a good physician-patient relationship and provide quality care. Various studies have shown that empathy varies depending on the country, the instrument used, the evaluator, and the HCW's specialty. This systematic review aims to estimate the levels of empathy among HCWs in South American countries between 2000 and 2019. Methods: We conducted searches in 15 databases (PubMed, Scopus, Web of Science, EMBASE, Scielo, PsycoInfo, ScientDirect, Latindex, and LILIACS), four preprint servers (medRxiv, bioRxiv, SportRxiv, and Preprints), and other search engines such as Dimensions (20), Google Scholar, Yahoo!, and Alicia CONCyTec (c). We followed the PRISMA guidelines, and this study was registered in PROSPERO (CRD42023454007). Results: Out of 18,532 documents identified from November 10 to 28, 2021, 10 articles were included (n = 2487 participants, of which 1989 were patients). Among the studies focusing on self-evaluated empathy, four relied on the Jefferson Scale of Empathy for medical professionals (JSE-HP). However, assessments from patients employing Jefferson Scale of Patient’s Perceptions of Physician Empathy (JSPPPE) and Consultation and Relational Empathy (CARE) scale suggested high levels of empathy We found that both professionals and patients perceived that empathic care was provided, often at a medium or regular level. Surgery residents presented lower levels of empathy compared to obstetrics-gynecology and pediatrics physicians. Conclusion: Empathy is crucial in determining the quality of care and patient satisfaction during healthcare services provided by HCWs. Therefore, it is important to support professionals so that the various stressful situations they encounter in their work and daily life do not negatively influence the approach they provide to patients.